Contribuições da análise do comportamento ao estudo do comportamento político - Cassas, Fernando Albregard (2007)
Literature in the field of Political Psychology has been worried, to a large extent, about the study of the phenomenon of the Political Participation, having as data the participants of a collective action. However, in the same way that a great number of participant people exists, a number also exists that does not enter the social movement, a layer of the population who does not adhere to the movement. On this subject it has few studies in scientific literature. Our interest is the questioning concerning about what it determines the political participation and not the participation in the Student Movement, looked at through the lens of Behavior Analysis. However, we come across with a methodological problem. Behavior Analysis does not appear in research in Political Psychology in Brazil, therefore it s necessary that let us justify this choice as validates. Therefore our object of work will be a theoretical description of how we can bring Behavior Analysis for Political Psychology, followed for a proposal of analysis of the participation and not participation in the student movement of the PUC/SP as an example about the application of this kind of analysis. We raise some important aspects: first of them it is the fact of, when analyzing the data, exists a search for relating events thus to explain a phenomenon; as a aspect that also it deserves to be commented is the quarrel that the Behavior Analysis brings on the validity of the verbal story as given of research. In synthesis, we describe here what we understand as the main contribution that the Behavior Analysis can bring to the study of the political behavior. This perspective of understanding of the phenomenon politician while a successive and interrelation process of events, brings a historical perspective to the event and relation between individual and basic environment for the understanding of the political behavior